Reeflections No. 26, September 1991 - (:unkn) unknown (Great Barrier Reef Marine Park Authority, 1991)
Newsletter of the Great Barrier Reef Marine Park Authority. Contens include: Crown-of-Thorns Latest, Cyclones Flooding Studies, Reef Education Awards, IUCN - Perth November 1990, Reef Pilots Now Compulsory, Inventory Award, The Understanding is Growing, The Run-off Flow-On Effects, The Human Touches, Human Influences on the Reef, Reef Biosearch, ACRS Annual Scientific Meetings, Adopting a Reef, Big Industry Questions, Seaweek '91, Passage Ways and Pollution Ways, Reviews, Current Issues in the World's Largest Marine Park.
Keywords: Communities; Education; People and the Reef; Coastal communities; Reef-wide